U-Pb detrital zircon ages of upper jurassic continental successions: Implications for the provenance and absolute age of the jurassic-cretaceous boundary in the Neuquén Basin - Naipauer, Maximiliano (2015)
New U-Pb detrital zircon ages are presented for the Tordillo Formation. The ages indicate that the most important source region of sediment supply was the Jurassic Andean arc (peaks at c. 144, 153 and 178 Ma), although two secondary sources were defined at c. 218 and 275 Ma. Temporal variation in the provenance indicates that at the beginning of the sedimentation, Carboniferous to Lower Jurassic magmatic rocks and Lower Palaeozoic metamorphic rocks were the most important sources. Towards the top, the data suggest that the Andean arc becomes the main source region. The comparison between provenance patterns of the Tordillo Formation and of the Avilé Member (Agrio Formation) showed some differences. In the former, the arc region played a considerable role as a source region, but this is not identified in the latter. The results permit a statistically robust estimation of the maximum deposition age for the Tordillo Formation at c. 144 Ma. This younger age represents a discrepancy of at least 7 Ma from the absolute age of the Kimmeridgian and Tithonian boundary (from the chronostratigraphic timescale accepted by the International Commission of Stratigraphy, IUGS), and has strong implications for the absolute age of the Jurassic-Cretaceous boundary.